1992
DOI: 10.1111/j.1439-0442.1992.tb00240.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Diets with Graded Levels of Deoxynivalenol on Performance in Growing Pigs

Abstract: Summary Feeding trials were conducted to evaluate the effect of including deoxynivalenol (DON)‐contaminated oats to provide approximately 0.5, 1.0, 2.0 and 4.0 mg/kg in the complete diets of growing pigs with initial weight of 25 kg. Performance was recorded as weight gain, feed intake, efficiency of feed utilization and carcass quality. Restricted feeding was compared to ad libitum feeding. For the groups fed diets containing 2 and 4 mg/kg of DON, a dose‐related decrease in weight gain was observed during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
2

Year Published

1993
1993
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(35 citation statements)
references
References 10 publications
3
29
2
Order By: Relevance
“…Pigs fed diets containing 2 and 4 mg kg −1 of DON exhibited a dose-related decrease in weight gain within the first 8 weeks (Bergsjo et al 1992). The 4 mg kg −1 diet caused decreased feed intake, weight gain, and efficiency of feed utilization throughout the experiment.…”
Section: Chronic Effectsmentioning
confidence: 99%
“…Pigs fed diets containing 2 and 4 mg kg −1 of DON exhibited a dose-related decrease in weight gain within the first 8 weeks (Bergsjo et al 1992). The 4 mg kg −1 diet caused decreased feed intake, weight gain, and efficiency of feed utilization throughout the experiment.…”
Section: Chronic Effectsmentioning
confidence: 99%
“…Pair-feeding studies with pigs indicate that at the lower dose ranges, the effects of DON on growth may be explained entirely by the effects on voluntary feed intake (Rotter et al, 1995). However, Prelusky (1997) concluded that at relatively high dietary concentrations of DON (above 9 mg/kg), the deleterious effects on weight gain may not be fully explained by the Bergsjo et al (1992), Friend et al (1992), Bergsjo et al (1993), Prelusky et al (1994b), Trenholm et al (1994), and Rotter et al (1995).…”
Section: Feed Refusal Emesis and Anorexiamentioning
confidence: 99%
“…1) have been conducted with Fusarium-contaminated grain and the effects tend to be greater with such diets than with those supplemented with the pure form of the mycotoxin. In at least two instances (Bergsjo et al, 1992(Bergsjo et al, , 1993 limited quantities of other trichothecenes such as 3-ADON and NIV were also present together with ZEN. It is may be significant that other trichothecenes including NIV and T-2 toxin have been implicated in both feed refusal and anorexia in pigs (Table 1).…”
Section: Jpf D'mello Et Al / Animal Feed Science and Technology 8mentioning
confidence: 99%
“…Previous studies concentrated primarily on T-2 toxin [for review see Taylor et al (1989)l while some recent work describing the effects of feeding DON-contaminated diets reported no significant changes in IgA levels (Bergsjo et al 1992(Bergsjo et al , 1993. When pigs were immunized with sheep red blood cells, a tendency was observed toward a delayed response in peak titers with increased DON contamination (Rotter et al 1994 (Trinchieri 1989).…”
mentioning
confidence: 99%